2009
DOI: 10.1007/978-3-642-02927-1_32
|View full text |Cite
|
Sign up to set email alerts
|

Incompressibility through Colors and IDs

Abstract: In parameterized complexity each problem instance comes with a parameter k, and a parameterized problem is said to admit a polynomial kernel if there are polynomial time preprocessing rules that reduce the input instance to an instance with size polynomial in k. Many problems have been shown to admit polynomial kernels, but it is only recently that a framework for showing the non-existence of polynomial kernels for specific problems has been developed by Bodlaender et al. [6] and Fortnow and Santhanam [17]. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
141
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 19 publications
1
141
0
Order By: Relevance
“…To prove our conditional non-existence result for Lobbying parameterized by (m, k), we employ an "incompressibility result" for Set Cover due to the work of Dom, Lokshtanov, and Saurabh (2009).…”
Section: Limits Of Preprocessingmentioning
confidence: 99%
See 3 more Smart Citations
“…To prove our conditional non-existence result for Lobbying parameterized by (m, k), we employ an "incompressibility result" for Set Cover due to the work of Dom, Lokshtanov, and Saurabh (2009).…”
Section: Limits Of Preprocessingmentioning
confidence: 99%
“…Dom et al (2009) showed that, unless NP ⊆ coNP/poly, Set Cover (SC) does not admit a polynomial kernel with respect to the combined parameter (|U|, h). To show that this result transfers to Lobbying with respect to (m, k) we describe a polynomial time and parameter transformation from SC with respect to (|U|, h).…”
Section: Limits Of Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…Dom et al [9] provide a framework to build composition algorithms by using "identifiers". One of the necessary conditions is the existence of an algorithm running in 2 p γ · poly time for the considered parameter p and a fixed constant γ.…”
Section: Parameterized Problem Is Compositional If There Is a Composimentioning
confidence: 99%